The brine shrimps (Artemia and Parartemia) of South Australia, including descriptions of four new species of Parartemia (Crustacea: Anostraca: Artemiina) - Timms, Brian V; Hudson, Peter (Zootaxa, 2009)
The Australian endemic brine shrimp Parartemia is more speciose than the literature suggests, with eight described species, four new ones added here from South Australia and many undescribed species elsewhere in Australia. P. acidiphila n. sp. occurs in acidic salinas on Eyre Peninsula, in the Gawler Ranges in South Australia and also in the Esperance hinterland, Western Australia, while P. auriciforma n. sp., P. triquetra n. sp. and P. yarleensis n. sp. occur in remote episodic salinas in western South Australia. Introduced Artemia franciscana and A. parthenogenetica are limited to present and defunct salt works; reports of Artemia beyond salt works in South Australia are enigmatic.